Cap-dependent translation is mediated by ‘RNA looping’ rather than ‘ribosome scanning’ - Jang, Sung Key (RNA Biol, 2015)
The 40S ribosomal subunit cannot directly recognize the start codon of eukaryotic mRNAs. Instead, it recognizes the start codon after its association with the 5′-cap structure via translation initiation factors. Base-by-base inspection of the 5′UTR by a scanning ribosome is the generally accepted hypothesis of start codon selection. As part of an effort to confirm the underlying mechanism of start codon selection by the 40S ribosome, we investigated the role of eIF4G, which participates in the recruitment of 40S ribosomes to various translation enhancers, such as 5′-cap structure, poly(A) tail, and several internal ribosome entry sites. We found that an artificial translation factor composed of recombinant eIF4G fused with MS2 greatly enhanced translation of an upstream reporter gene when it was tethered to the 3′UTR. These data suggest that the 40S ribosome recruited to a translation enhancer can find the start codon by looping of the intervening RNA segment. The ‘RNA-looping’ hypothesis of translation start codon recognition was further supported by an analysis of the effect of 5′UTR length on translation efficiency and the mathematically predicted probability of RNA-loop–mediated interactions between the start codon and the 40S ribosome associated at the 5′-end.